Demonstration of Low-Temperature Fine-Pitch Cu/SiO₂ Hybrid Bonding by Au Passivation - Demin Liu; Po-Chih Chen; Tzu-Chieh Chou; Han-Wen Hu; Kuan-Neng Chen (IEEE Journal of the Electron Devices Society, 2021)
Fine pitch Cu/SiO2 hybrid bonding has been successfully demonstrated at a low temperature of 120 °C, a breakthrough, using Au passivation method in this work. To explore the bonding mechanism of passivation structures for hybrid bonding in details, Cu-Cu direct bonding with Au passivation on both wafer-level and chip-level has been discussed, including analyses of AFM, SAT, TEM, electrical measurements, and reliability test. Cu/SiO2 hybrid bonding with the fine pitch structure with stable electrical performance can be achieved at low bonding temperature under an atmospheric environment. Accordingly, this Au passivation scheme for Cu/SiO2 hybrid bonding with excellent bonding quality, low thermal budget, and high reliability shows a great feasibility for the 3D IC and heterogenous integration applications.